2007
DOI: 10.1002/anie.200702206
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Cross‐Coupling of Alkyl Halides with Alkenyl Grignard Reagents

Abstract: Cheap and safe: An iron‐catalyzed cross‐coupling reaction between alkyl halides and alkenyl Grignard reagents is described. This CC bond coupling reaction is promoted by the cheap and nontoxic FeCl3 and displays good tolerance against various functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(56 citation statements)
references
References 35 publications
0
53
0
3
Order By: Relevance
“…These results indicated that the cross-coupling reaction catalyzed by complex 1 could involve a radical mechanism in the reaction of alkyl halide with the iron species. 6b, 15,16 In our system, the slow addition of phenylmagnesium bromide to the reaction mixture is unfavorable for the formation of the cross-coupled product (Table 1). This procedure resulted in increase of the formation of biphenyl, the homocoupled product.…”
mentioning
confidence: 90%
“…These results indicated that the cross-coupling reaction catalyzed by complex 1 could involve a radical mechanism in the reaction of alkyl halide with the iron species. 6b, 15,16 In our system, the slow addition of phenylmagnesium bromide to the reaction mixture is unfavorable for the formation of the cross-coupled product (Table 1). This procedure resulted in increase of the formation of biphenyl, the homocoupled product.…”
mentioning
confidence: 90%
“…[39] From 1-bromo-2-methylprop-1-ene (0.135 g, 1 mmol), ndodecylboronic acid (0.428 g, 2 mmol), Pd complex (0.02 mmol) and Cs 2 CO 3 (0.652 g, 2 mmol), 6 was obtained in 63% (0.141 g) yield. 1 (Z)-Pentadec-2-ene (7) [40] From (Z)-1-bromoprop-1-ene (0.121 g, 1 mmol), n-dodecylboronic acid (0.428 g, 2 mmol), Pd complex (0.02 mmol) and Cs 2 CO 3 (0.652 g, 2 mmol), 7 was obtained in 62% (0.130 g) yield.…”
Section: -Methylundec-2-ene (5)mentioning
confidence: 99%
“…1.36-1.16 (m, 12H), 0.88 (t, J = 7.5 Hz, 3H). [39] From 2-bromopropene (0.121 g, 1 mmol), n-dodecylboronic acid (0.428 g, 2 mmol), Pd complex (0.02 mmol) and Cs 2 CO 3 (0.652 g, 2 mmol), 11 was obtained in 64% (0.135 g) yield.…”
Section: -Methyldec-1-ene (10)mentioning
confidence: 99%
“…42) Tosylate 13 was treated with lithium bromide to give 16 and the trans-isomer in 55% and 27% yield, respectively (Chart 6). The relative configuration of the products was determined by nOe experiments (see Experimental).…”
Section: Thiol-mediated Acyl Radical Cyclizationmentioning
confidence: 99%